Comparison of Palm Oil Export Determinants between Indonesia and Malaysia - Hasanudin Hasanudin; Yanto Yanto (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
Indonesia's foreign trade, especially export activities, covers various economic sectors. One of them is in the agricultural sector. One of the most important economic sectors is the plantation sub-sector, namely oil palm plantations. Currently, palm oil exports are very important given the increasing volume. The novelty of this research is that it tries to explore further the conditions of Indonesian palm oil exports and the factors or determinants that determine the world's palm oil demand. Research on palm oil exports is for identifying trade patterns between Indonesia and Malaysia from the perspective of the factors that influence it. The results showed that the GDP factor both affected the export volume of Indonesian and Malaysian palm oil, but had a different coefficient or slope sign. This means that there is a substitution relationship between Indonesia and Malaysia, that is, the Malaysian market share switches to the Indonesian market share. The GDP similarity index factor that affects the volume of Malaysian palm oil exports shows a negative sign or slope. This may imply that Malaysian palm oil exports have the potential to increase trade that is inter-industry or different in industry. The relative distance factor only affects the volume of Indonesian palm oil exports. This means that distance or transportation costs play an important role in Indonesian trade, especially Indonesian palm oil exports. The implications of this research are, among others, it is important to increase trade cooperation more intensively. For this reason, Indonesia must be able to control the market share that is the destination for CPO exports by continuing to establish and develop cooperation in the potential agricultural sector, for example oil palm plantations, both in the upstream and downstream industries. In addition, Indonesia must be able to carry out a more productive trade process, and build good infrastructure, so that the trade transaction process becomes more effective and efficient, and provides far greater benefits to its partners.Keywords: International Trade; Palm Oil; Exports